Kajian Tentang Kinetika Transfer Asam Asetat Pada Antarmuka Cair-Cair Dengan Menggunakan Rotating Membrane Cell - Hendrawan Hendrawan (Institut Teknologi Bandung, 2002)
This work concerns the technique of rotating membrane cell (RMC) as an absolute technique to study the kinetic of solute transfer between liquid-liquid phases and its application to investigate the effect of an inert electrolyte on transfer of acetic acid (AA) from aqueous phase containing various concentrations of added salt into isopropyl myristate (IPM). Testing of the method using a fast transfer system and a set of autodiffusion experiment confirm its validity, and show an excellent control of hydrodynamics. For the case of acetic acid transfer, it is found that the added salt plays a significant role in the process occurring at the liquid-liquid interface, leading to an expression of BrÃ¶nsted`s kinetic hypothesis type.